New variable gain super-twisting sliding mode observer for sensorless vector control of nonsinusoidal back-EMF PMSM. (July 2016) - Baratieri, Cassio Luciano; Pinheiro, Humberto
Abstract: This paper presents a new discrete-time super-twisting sliding mode observer with variable gains for sensorless nonsinusoidal vector control of permanent magnet synchronous motors. This observer is adopted to estimate the back electromotive forces (back-EMF) that are required for the rotor speed estimation and for the nonsinusoidal vector control. In addition, their gains are time-varying to minimize the chattering. So, they are adjusted based on internal states of the super-twisting algorithm. The stability analysis is investigated from the Lyapunov theory for discrete-time systems. Finally, simulation and experimental results are presented to demonstrate the good performance and the effectiveness of the proposed observer. Abstract : Highlights: A new discrete-time super-twisting SM observer with variable gains is proposed. Variable gains can mitigate adequately the residual chattering. The discrete-time stability analysis demonstrates that the observer is stable. The method is implemented in an experimental platform with a fixed point DSP. Experimental results verify the effectiveness of the proposed observer.